Sistem Instrumentasi Pada Pendeteksian Tangan dan Monitoring Tangki Persediaan Alat Cuci Tangan Otomatis Menggunakan Photovoltaic - Anggia Bunga Pertiwi Kakiay; Dian Budhi Santoso; Ulinnuha Latifa (Electro Luceat, 2020)
Clean and Healthy Living Behavior is all health behaviors carried out on the awareness and application of PHBS can start from a very simple thing namum has a great impact e.g. Hand Washing Using Soap. Properly practiced hand washing is the easiest and most effective way to prevent a wide range of diseases. It uses an arduino microcontroller, an infrared sensor used to detect hands, an ultrasonic sensor as a detector on a tank and an I2C LCD as an interface. This proximity sensor is capable of detecting hands from a distance of 3-12 cm. While ultrasonic sensors are able to detect the in-tank in-tank with sensor readability with actual values of 99.68% for water tanks and 99.61% for soap tanks. I2C 16x2 LCD is capable of displaying monitoring level in the form of 0-100% percentage.